Immunolocalization of steroidogenic enzymes in the vaginal mucous of Galea spixii during the estrous cycle - Amilton Cesar dos Santos; Alan James Conley; Moacir Franco de Oliveira; Gleidson Benevides Oliveira; Diego Carvalho Viana; Antônio Chaves de Assis Neto (BMC, 2017)
Abstract Background The synthesis of sex steroids is controlled by several enzymes such as17α-hydroxylase cytochrome P450 (P450c17) catalyzing androgen synthesis and aromatase cytochrome P450 (P450arom) catalyzing estrogen synthesis, both of which must complex with the redox partner NADPH-cytochrome P450 oxidoreductase (CPR) for activity. Previous studies have identified expression of steroidogenic enzymes in vaginal tissue, suggesting local sex steroid synthesis. The current studies investigate P450c17, P450aromatase and CPR expression in vaginal mucosa of Galea spixii (Spix cavy) by immuno-histochemical and western immunoblot analyses. Methods Stages of estrous cyclicity were monitored by vaginal exfoliative cytology. After euthanasia, vaginal tissues were retrieved, fixed and frozen at diestrus, proestrus, estrus and metestrus. The ovaries and testis were used as positive control tissues for immunohistochemistry. Results Data from cytological study allowed identification of different estrous cycle phases. Immunohistochemical analysis showed different sites of expression of steroidogenic enzymes along with tissue response throughout different phases of the estrous cycle. However, further studies are needed to characterize the derived hormones synthesized by, and the enzymes activities associated with, vaginal tissues. Conclusion Current results not only support the expression of enzymes involved in sex steroid synthesis in the wall of the vagina, they also indicate that expression changes with the stage of the cycle, both the levels and types of cells exhibiting expression. Thus, changes in proliferation of vaginal epithelial cells and the differentiation of the mucosa may be influenced by local steroid synthesis as well as circulating androgens and estrogens.